Mekanisme Hukum : Perdagangan Karbon Melalui Bursa Karbon di Indonesia - Valiant, Valiant Alfarizy; Mariyatul Ulfa, Sayyidah; Liyadi, Syerra S.; Farahiya, Zhafira; Ludiasa, Rohmad (LPPM Universitas Ekasakti Padang, 2023)
Indonesia shows its commitment to the Paris Agreement held in 2016 on climate change. One of the implementations of this agreement, Indonesia has implemented carbon trading which carbon trading is one part of the mitigation to slow down climate change as well as realizing the target together with participating countries of 2 - 1.5 Celsius or with a percentage of 29% and 41% in 2030 and net zero emissions by 2060. Scientific research uses legal research methods, relying on the analysis of rules, norms, jurisprudence, and jurisprudential opinions. Moving on from the mandate of Law 14/2023 concerning the Development and Strengthening of the Financial Sector, OJK issued POJK Number 14 of 2023 concerning Carbon Trading through the Carbon Exchange. The POJK contains procedures for carbon trading through the carbon exchange, as well as regulation, licensing, supervision, and development of carbon trading through the carbon exchange.